2020
DOI: 10.1021/acsami.0c05333
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Superelastic Fibrous Sponges Tailored by “Stiff–Soft” Bicomponent Electrospun Fibers for Warmth Retention

Abstract: Health risks in an extremely cold environment make warm retention equipment highly desirable. However, creating materials with a high warm retention performance and robust mechanical property to durably prevent against the harsh conditions is highly challenging. Herein, we report on a one-step and facile strategy to fabricate stretchable and superelastic fibrous sponges by creating unique “stiff–soft” polymer networks within fibers and bonding architecture among fibers. The premise of this design is that stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…[31] It was found that the BC molecules have shorter distances between the corresponding oxygen atom and hydrogen atom than that of SiO network, suggesting that the adjacent BC nanofibers have stronger interaction than SiO 2 nanofibers. [32] This conclusion was also proved by the calculated results of interaction energies, the counterpoise-corrected interaction energy of BC molecules was found to be −13.7 kcal mol −1 , much lower than that of the SiO network (−11.93 kcal mol −1 ), suggesting that the BC nanofibers were more likely to close together and finally form a nanonet structure.…”
Section: Formation Mechanism and Structural Regulation Of Cage-like Architecturementioning
confidence: 58%
“…[31] It was found that the BC molecules have shorter distances between the corresponding oxygen atom and hydrogen atom than that of SiO network, suggesting that the adjacent BC nanofibers have stronger interaction than SiO 2 nanofibers. [32] This conclusion was also proved by the calculated results of interaction energies, the counterpoise-corrected interaction energy of BC molecules was found to be −13.7 kcal mol −1 , much lower than that of the SiO network (−11.93 kcal mol −1 ), suggesting that the BC nanofibers were more likely to close together and finally form a nanonet structure.…”
Section: Formation Mechanism and Structural Regulation Of Cage-like Architecturementioning
confidence: 58%
“…25 The obtained bicomponent PS/PU fibrous sponges showed good elasticity with only a slight plastic deformation of 4.9% after the 100 cyclic fatigue compression test. 26 However, the fibrous sponges suffered unsatisfactory thermal conductivity because of large fiber diameters (>2 μm). In addition, the sponges burned easily and generated melt droplets, leading to existing security risks.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the mechanical properties, the polyurethane (PU) elastomer has been introduced into the PS fibrous sponges . The obtained bi-component PS/PU fibrous sponges showed good elasticity with only a slight plastic deformation of 4.9% after the 100 cyclic fatigue compression test . However, the fibrous sponges suffered unsatisfactory thermal conductivity because of large fiber diameters (>2 μm).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its diverse excellent properties, these 3D sponges have an increasing number of applications including pressure sensor, 19 biodegradable scaffolds, 20 microwave absorbers 21 and warmth retention materials. 22 Among these developing applications, electrospinning 3D sponges have been considered as an effective adsorbing material for organic compounds. For instance, aerogels are prepared by adding SiO 2 nanoparticles to 3D electrospinning polyacrylonitrile (PAN) nanofiber aerogels, and the prepared PAN/SiO 2 aerogels have the characteristics of superhydrophobic/ superoleophilic that the surfactant stabilized oil droplets can be effectively separated from the aqueous emulsion because of its excellent flux and high separation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This method was first reported by Si group in 2014, thus opening up a new field of research. Owing to its diverse excellent properties, these 3D sponges have an increasing number of applications including pressure sensor, 19 biodegradable scaffolds, 20 microwave absorbers 21 and warmth retention materials 22 …”
Section: Introductionmentioning
confidence: 99%